A Benign Cardiac Growth but Not So Indolent - Adil S. Wani; Sahadev T. Reddy; Lakshmi Harinath; Robert W. W. Biederman (Case Reports in Cardiology)
Cardiac lipomatous hypertrophy is a rare benign condition that usually involves the interatrial septum. Due to its benign nature it rarely requires intervention. Its presence outside the interatrial septum is reported infrequently. We present a case of lipomatous hypertrophy in the intraventricular septum that was complicated by a severe, symptomatic, and disabling dynamic left ventricular outflow tract obstruction. The symptoms significantly improved following the excision of the mass. In our case transthoracic echocardiogram was used to visualize the mass and measure the severity of the obstruction; Cardiac Magnetic Resonance Imaging was used to characterize the mass and histopathology confirmed the diagnosis.